Regional integration and cultural industries : their interdependence - Bully, Alwyn (CCS GeorgetownGY, 1994)
Identifies three steps that cultural activists must take to be a catalyst to the integration process. Highlights the role of the media and the use of telecommunications in the integration process. Focuses on the need for persons to be proficient in several languages of the region; freedom of movement from one country to the next; and, the removal of heavy taxes.